Relationship of hepatitis C risk to hepatitis C test acceptance among adult patients participating in an ED hepatitis C screening programme. Issue 5 (2nd January 2023) - Cowan, Ethan; Brandspiegel, Samantha; Araki, Benjamin; O'Brien-Lambert, Clare; Merchant, Roland; Buckler, David G; Eiting, Erick; Calderon, Yvette
Abstract : Background: It is possible that adult ED patients consider their hepatitis C virus (HCV) risk factor history when deciding whether to accept HCV screening. To help address this question, we examined whether self-reporting any HCV risk was more common among ED patients who agreed than who declined HCV screening. Among ED patients who agreed to HCV screening, we also assessed if self-reporting any HCV risk was more common among those whose HCV antibody (Ab) and HCV viral load (VL) test results were positive. Methods: This study was conducted among adult patients ≥18 years old participating in a universal, ED-based HCV screening programme in New York City between 22 January 2019 and 9 April 2020. Participants were surveyed about their HCV risk factors. Differences in the frequencies of self-reporting any HCV risk were compared according to HCV screening acceptance and by HCV Ab and VL status. Results: Of the 4658 ED patients surveyed, 2846 (61%) accepted and 1812 (39%) declined HCV screening. Among these participants, 38% reported at least one HCV risk factor, most commonly injection drug use. Self-reporting any HCV risk was not more common among those who accepted versus declined HCV screening (40% vs 37%, p<0.7) but was more common among those with HCV Ab positive versus negative test results (36% vs 6%, p<0.001) and HCV VL positive versus negative results (95% vs 5%, p<0.001). Conclusion: HCV risk factors were self-reported by more than one-third of ED patients but were not more commonly present among those who accepted HCV screening.